Effects of microwave irradiation of Fagopyrum tataricum seeds on the physicochemical and functional attributes of sprouts. (1st August 2022) - Ma, Hui; Xu, Xianmeng; Wang, Shunmin; Wang, Junzhen; Wang, Simeng
Abstract: The effects of microwave-preexposing Tartary buckwheat seeds on their germination, including nutritional and functional attributes were investigated. The results showed that microwave irradiation (300 W/50 s) accelerated the germination process. Germination caused a 7.51-fold increase in reducing sugar content and a 69.61% reduction in starch content, accompanied by significantly enhanced amylase activity, which was amplified by 300 W/50 s microwaving. Microwave also enhanced the levels of various amino acids (especially at 300 W/50 s) and fatty acids (especially at 550 W/75 s) during germination. Enhancements of phenylalanine ammonia-lyase (PAL), chalcone isomerase (CHI), and flavonol synthetase (FLS) activities were observed with microwave irradiation, and maximum total flavonoid content (5.15 g/100 g dry weight; 31.78% higher than that of the control) was reached after irradiation at 300 W/50 s. In addition, the antioxidant capacity and the tyrosinase and acetylcholinesterase inhibitory activities were enhanced. Principal component analysis indicated that changes in flavonoids, PAL, CHI, and FLS were highly correlated with antioxidant capacity and enzyme inhibitory activities. Therefore, microwave irradiation is an efficient protocol for enhancing the physicochemical and functional attributes of edible Tartary buckwheat sprouts. Highlights: Microwave irradiation (300 W/50 s) accelerated the starch hydrolysis of sprouting Fagopyrum tataricum seeds. Microwave irradiation enhanced the EAA and UFA content in Fagopyrum tataricum sprouts. The levels of flavonoids, PAL, CHI, and FLS were enhanced by microwave pretreatment. The antioxidant capacity and enzyme inhibitory activities were enhanced by microwave pretreatment.